Pelatihan Sistem Pembukuan Berbasis Komputer Bagi Tim Pengelola Koperasi Sahabat Literasi Flobamorata - Tena, Silvester; Galla, Wellem Fridz; Nursalim, Nursalim; Sampeallo, Agusthinus S (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Nusa Cendana, 2024)
Empowering Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) is strategic to boost the national economy. East Nusa Tenggara (ENT), as one of the cooperative provinces, is experiencing rapid growth in both quantity and quality. As pillars of regional and national economics, Cooperatives need to be developed, especially for small communities, in their various productive businesses. The development of cooperatives in NTT Province is quite significant until 2023, namely 4,301. Three thousand eight hundred sixty-six cooperatives are legal entities and active, while 435 cooperatives are not yet legal entities. The Koperasi Simpan Pinjam Sahabat Literasi Flobamorata (KSP Batera) is an institution founded by members who have the same destiny and share the same responsibility in the economic field. Its development is quite advanced regarding assets and the number of members. The main problem faced by KSP Batera is that financial management is still manual, and an Annual Member Meeting (AMM) has yet to be held. This happens because the educational background is inappropriate, and there needs to be more knowledge about the Cooperative Financial Accounting System (CFAS). Training activities for the management team on a computer-based financial accounting bookkeeping system is the best solution for the future development of this cooperative. The final result of the training activity is that the management team can complete a computer-based bookkeeping system and financial reports and prepare AMM reports to be accounted for after the close of the financial year. Maximum knowledge transfer occurs because the learning model in the form of theory and practice is 30% and 70%, respectively. Apart from that, assistance is also provided for managers both offline and online